Beyond Disorder: Stigma and Identity Across the Substance Use Health Spectrum in a Public Health Framework - Tanisse Epp; Mya Duffy; Kim Hellemans (Substance Use & Addiction Journal, 2026)
Background: Despite the widespread prevalence and health impacts of substance use (including alcohol), policies and services remain anchored in diagnostic criteria, overlooking people whose substance use does not fit clinical categories. This structural emphasis on meeting diagnostic thresholds often means people wait until crisis to seek help rather than engaging with support earlier. Substance use health frameworks instead encourage understanding substance use as an aspect of health that occurs along a continuum rather than a simple binary between “healthy” and “disordered” making visible a wider range of experiences and outcomes. While there is early adoption of this framework, little is known about how people understand their place on this spectrum or how it shapes their relationships with substances, identity, and stigma. Methods: Semi-structured focus groups were conducted with men and women across the substance use health spectrum (n = 18). Codebook thematic analysis was used to identify dominant narratives about substance use, identity, and stigma. Results: Participants described diverse and shifting relationships with substances, including individuals who do not currently or have never used substances (n = 7), who have a relationship with one or more substances (n = 8), and who notice a change in their health with regard to their substance use (n = 3). Analysis generated four themes: spectrum identity negotiation and fluidity; social contexts, norms, and hierarchies; negotiating stigma across public, self, and structural levels; and gendered patterns in substance use discussions. Conclusion: The substance use health spectrum offers language for describing substance use as a dynamic aspect of health and identity rather than a fixed diagnostic status. By exploring how people across the continuum understand and negotiate stigma, our findings show how the spectrum can inform public health messaging, services, and research that reflect substance use across the population and move stigma reduction beyond disorder‑focused approaches.